(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
The historical work of Alfredo Breceda remains unrecognized. The yore and con- temporary Mexican revolution historiography has not taken him and many others into account. Altogether men, women and children who witnessed the Mexican revolution war remain unknown. Mexico revolucionario, his masterpiece, it is an attempt to show an objective and well presented political history of the early years of the Mexican revolution as well as the beginnings of the first constitutionalist stage. Despite he was Venustiano Carranza follower, he attempted to avoid and overcome the influences that made him to be less objective and un: torical testimony. The first volume was published in 1920, and the second one in 1941, that’s why his books clearly shows a tour of the main military, diplomatic and gubernatorial events of the revolutionary leaders.